Fabrication of fluorinated polyamide seawater reverse osmosis membrane with enhanced boron removal - Li, Can (2023)
Developing a reverse osmosis membrane with desirable water/salt selectivity and boron removal has been recognized as crucial for high-efficient seawater desalination. Herein, fluorinated seawater reverse osmosis (SWRO) membranes were fabricated via fluorine-containing monomers-mediated interfacial polymerization or surface modification by grafting fluorine-containing monomers atop nascent polyamide (PA) layer via a second interfacial reaction. The fluorinated molecules, 5-(trifluoromethyl)-1.3-phenylenediamine (TFPD), 3,5-bis(trifluoromethyl) benzoyl chloride (TFBC) or 2,2,2-trifluoroethylamine (TFEA), were confirmedly integrated into the PA matrix presumably via strong chemical covalent bonds, which manipulated the physicochemical properties of the PA layer, including surface hydrophilicity, pore size distribution, cross-linking degree and interactions between membrane and solutes, thereby producing a high-selectivity thin-film composite (TFC) membrane. The optimized membranes, i.e., TFC-TFPD, TFC-TFBC and TFC-TFEA, presented significantly excellent separation performance than the control and commercial membrane, both in water/salt selectivity and boron removal capability, accompanied by a comparable water permeance. Among the three proposed incorporation method of fluorinated monomers, direct grafting of TFEA upon the nascent PA layer demonstrates the best efficiency in introducing fluorine elements in the TFC PA membranes, compared to the addition of TFPD and TFBC into aqueous and organic phases during IP process, respectively. The fluorine-incorporated strategy employed in this present work offered a new design of the PA layer containing fluorinated molecules to obtain the desired permselectivity of TFC SWRO membranes towards efficient removal of salt and boron acid in seawater desalination.